Automação da máquina Poly Clip aplicadora de grampos em embutidos - Jesus, Edson Francisco de (2014)
This paper presents a project to improve the control of a machine stapler of embedded products, Poly Clip the machine, which operates 18 hours a day for six days of the week. The sequence of machine operations is controlled by the PLC Siemens S7-200 model, where the same controls all output signals of the machine according to the conditions of the signals of the sensors. The major focus of the project is the improvement of the main electrical panel and also the switchboard operator, which consists of buttonholes. The work to replace the PLC Siemens, by a brand Allen Bradley PLC Model 1200 micrologix and a control unit, improving the reliability of equipment and maintainability, bug fixes and operational process, avoiding wastage and reducing production costs.